1997
DOI: 10.1002/(sici)1097-0142(19970401)79:7<1428::aid-cncr21>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative clinical efficacy and safety of a novel controlled-release oxycodone formulation and controlled-release hydromorphone in the treatment of cancer pain

Abstract: Controlled-release oxycodone demonstrated excellent pharmacodynamic characteristics, analgesic efficacy, and safety as compared with controlled-release hydromorphone and represents an important new therapeutic option for cancer pain management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(55 citation statements)
references
References 36 publications
1
54
0
Order By: Relevance
“…Five randomized, double-blind clinical trials compared the efficacy of controlled-release oxycodone with other long-acting opioids (Table 3). 3,[15][16][17][18] Four of them compared controlledrelease oxycodone with controlled-release morphine; no difference in analgesic efficacy between the two treatments was found. 3,15,16,18 One study reported a higher frequency of itching and scratching with morphine than with oxycodone.…”
Section: Safety and Efficacy Of Oxycodone Compared With Other Opioidsmentioning
confidence: 99%
“…Five randomized, double-blind clinical trials compared the efficacy of controlled-release oxycodone with other long-acting opioids (Table 3). 3,[15][16][17][18] Four of them compared controlledrelease oxycodone with controlled-release morphine; no difference in analgesic efficacy between the two treatments was found. 3,15,16,18 One study reported a higher frequency of itching and scratching with morphine than with oxycodone.…”
Section: Safety and Efficacy Of Oxycodone Compared With Other Opioidsmentioning
confidence: 99%
“…Treatment preference did not differ significantly between CR oxycodone and CR morphine,18 19 CR oxycodone and CR hydromorphone,22 or between intravenous oxycodone followed by IR oxycodone and intravenous morphine followed by IR morphine 25 26. Gabrail et al reported no data for participant preference but found that 78.3% of participants rated oxycodone as ‘excellent,’ ‘very good’ or ‘good’ with 86.4% of the participants giving oxymorphone such ratings 20 21…”
Section: Resultsmentioning
confidence: 84%
“…Five studies either did not report adverse events or did not report them in a manner so they could be scrutinised for (and potentially included in) an evidence synthesis 12 16–19 27. One study only reported four adverse events in a transparent manner 22. The participants appeared to be adequately titrated in the majority of the studies,12 13 18–27 29–32 35–38 40–42 although this was unclear in four studies,16 17 28 34 and not the case in one study 33.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations